1993
DOI: 10.1088/0963-0252/2/1/010
|View full text |Cite
|
Sign up to set email alerts
|

A computational investigation of the RF plasma structures and their production efficiency in the frequency range from HF to VHF

Abstract: The influence of driving frequency on discharge structure and production efficiency has been investigated in Ar over the frequency range from 13.56MHz to l00MHz in terms of the relaxation continuum model. Under constant RF voltage, the plasma density increases in proportion to the square of the driving frequency. The net ionization and excitation rates, and the power density, show the same frequency dependence, although the collisional production efficiency per input power density is almost invariant with chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…{0 but R=0. Then, under the combined operations (10), the nonlinear system (1), (3), (4), (5) is form invariant, and we deduce that…”
Section: Nature Of the Problem Symmetries (I) Statement Of The Problemmentioning
confidence: 89%
See 2 more Smart Citations
“…{0 but R=0. Then, under the combined operations (10), the nonlinear system (1), (3), (4), (5) is form invariant, and we deduce that…”
Section: Nature Of the Problem Symmetries (I) Statement Of The Problemmentioning
confidence: 89%
“…plasmas the space-charge field is strong, especially in the sheath regions near the boundaries, and the full moment equations of Section 4 must be solved simultaneously with Poisson's equation (4). Neither can it generally be assumed that spatial variations are weak and therefore gradients of properties in the moment equations cannot be treated using the simplifying assumptions of the hydrodynamic regime and associated density gradient expansions.…”
Section: Modeling Rf Plasmas Swarm Date Rct Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 The VHF power supply direct to the substrate will be limited to ϳ100 MHz due to a technological difficulty in keeping a radial uniformity of the surface potential while increasing the frequency. Plasma driven by a frequency of more than several hundred MHz will be, therefore, maintained by the aid of several types of antennas.…”
Section: B Modeling Validitymentioning
confidence: 99%
“…Though conventional GDPs for spectrometric analysis have usually been operated at a driving frequency of 13.56 MHz, 11 several investigations using various frequencies have reported that the supplied frequency had a pronounced influence on the properties of the r.f.-GDP employed in sputter etching or surface treatment technologies. 14,15 Also in r.f.-GD-OES, Lazik and Marcus, 16 and Heintz and Hieftje 17 have demonstrated the influence of the driving frequency on several characteristics of the r.f.-GD-OES such as the sampling rate and the emission intensities, indicating that the driving frequency could affect such properties greatly and should be optimized for a particular application of the r.f.-GDP device. Matsuta et al reported on the unique properties of a 40.68-MHz r.f.…”
mentioning
confidence: 99%